(untitled) (GYMNASIUM, 2011)
Starting with the premise that the organization of sporting-recreational activities is an educational polyvalent activity which has to contribute to the enlargement of the knowledge horizon, to the forming of the practical skills, to the development of the perceptive skill, of the thought and initiative, as well as to the stimulation of the pupils’ interest for the independent, recreational activity, I recommend attention in establishing the objectives of this activity so that it meets the possibilities and the concerning of the pupils. Our research confirms this thing, namely the fact that the development of a tourist area cannot be realized without the multitude of the recreational sporting activities which have the purpose to improve the all-round education, acquiring knowledge, openness to socialize, love and respect for nature. In this way the cultural, natural and tourist potential is better known and improved in Arges county, by using intensively the forms of tourism, accessible to different categories of citizens, both in forming and shaping the human personality and in incomes growth, the tourism being one of the main gainful sources.